Rheological Behavior of Air in the Two-Pass Solar Collector - Dhaundiyal, Alok (Frontiers in Energy Research, 2022)
This study pivoted on the flow behavior of air streams across solar air collectors provided with wooden baffles under the absorber plates. The two-pass system was used for both flat and finned surfaces. The von Kármán momentum integral and Blasius equations were solved with the help of PDPE and ODE45 techniques. The solution was assumed to be a part of the initial value problem (IVP). The energy analysis of both solar air collectors was carried out using the Hottel–Whillier–Bliss equation (HWB) equation. The Sankey diagram was used for energy distribution across the solar collectors. The gray box modeling approach was adopted to comprehend the airflow behavior across the channel. The objective of this study is to examine the intrinsic behavior of the proposed design. The displacement of boundary to compensate for the momentum of air stream (θt) decreased by 31.25%–62.50% with an increase in mass flow rate (m)˙of 24.69%–49.38% for the flat plate collector (FPC). Similarly, the shear stress posed by the absorber plate (τw) dropped by 15.89%–37.20% with the augmentation of the mass flow rate. The momentum thickness for the flat plate with triangular fin (FPTF) increased relatively by 31.25%, compared to FPC at 8.10 g·s−1. The estimated value of collector efficiency (ηI) FPTF soared up by 4%–11.51% when it was juxtaposed against the corresponding values derived for FPC. The wall shear stress near the absorber plate followed that of a second-order Gaussian model. It was noticed in this study that the addition of the fin slowed down the shear effect and the momentum defect of airstream at the same mass flow rate.